Recurrent Metastatic Pulmonary Synovial Sarcoma during Pregnancy: A Case Report and Literature Review - Silvia De Rocco; Jasmine Di Biasi; Ilaria Fantasia; Sara Tabacco; Enrico Ricevuto; Pierpaolo Palumbo; Ilenia Imbergamo; Manuela Ludovisi; Maurizio Guido (Diagnostics, 2024)
Primary pulmonary synovial sarcoma is a rare type of soft tissue tumor. Exceptionally it can occur during pregnancy, representing a challenge in management and treatment given its notable aggressiveness and the not infrequent incidence of maternal death. We report our case of metastatic recurrence of pulmonary synovial sarcoma during pregnancy, with the aim to emphasize the decision-making, diagnostic, and therapeutic multidisciplinary processes and the evolution of the pathology. Besides, we focused on the analysis of the limited literature data available on the topic.